Impact of Nationwide Lockdown on Students of Higher Education - Jasbir Singh; Rahul Kundal; Neharica Subhash (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Following the onset of the COVID-19 pandemic in India, the Union Government of India announced nationwide lockdown. As the nationwide lockdown was implemented in India from 25th of March 2020, almost every sector of the Indian economy came to a halt. Along these circumstances, all kinds of educational institutions were also shut down. Evidently, and as anticipated, the students were among those groups that suffered the most during nationwide lockdown. Consequently, learning status of the students was hard-hit. The present study is an attempt to measure the impact of nationwide lockdown on the learning status of the students who were pursuing undergraduate and postgraduate courses at the University of Jammu at the time of announcement of nationwide lockdown. In order to collect data for the present study, an online questionnaire was developed using the Google Forms platform and link of the questionnaire was provided to 300 students who were pursuing undergraduate and postgraduate courses at the University of Jammu at that time. The responses from the students were received between 20th of August 2020 and 26th of August 2020. The data were then tabulated and analysed. It was observed that a large proportion of the respondents could only complete half of their syllabus (or even less) through online learning mode during nationwide lockdown, and that they had to face a variety of problems, such as anxiety, poor physical heath, poor internet connectivity, etc. It is suggested that the governments and the concerned authorities must aim to make policies to establish a resilient educational structure that is able to tackle situations like the COVID-19 pandemic and nationwide lockdown, so that the young mind’ productivity is not compromised.